Angka Kejadian serta Faktor-Faktor yang Mempengaruhi Gangguan tidur (Insomnia) Pada Lansia di Panti Sosial Tresna Werda Wana Seraya 1 Denpasar Bali Tahun 2013 - Arysta Dewi, Putu; Indah Ardani, I Gusti Ayu (E-Jurnal Medika Udayana, 2015)
Background: the incidence Rate of insomnia will increase as you get older. In the other words, the symptoms of insomnia often occurs in the elderly even almost half of the number of elderly reported having difficulty starting and maintaining sleep. Objective: to know the numbers of elderly who experience sleep disorders (insomnia) and the factors that affect sleep disorders (Insomnia) in Panti Tresna Werda Wana Seraya Denpasar. Materials and methods: a method of this research using design descriptive  of cross-sectional non-experimental, which use of samples 15 peoples after in inclusion and exclusion. Through live interview by using a questionnaire at Panti Tresna Werda Wana Seraya Denpasar. Result : There are 6 elderly (40%) who suffering insomnia with several factors affecting based on age,  there are 4 elderly 60 – 70 years (66,6%), there are 2 elderly 71 – 80 years (22,2%). Based on sex, there are 1 elderly man (25%) and 5 elderly women (45,5%).  Based on bad habit of sleeping, there are 1 elderly (16,6%) that has bad habit or bad sleeping patterns. Based on the underlying disease, there are 4 elderly (66,6%). Based on mental disorder such as major depression or  anxiety , there are 3 elderly or only 50% who having depression or anxiety.
Keywords: Insomnia, Elderly , Several Factors Affecting Insomnia